A SPEECH ACTS ANALYSIS OF THE UKRAINIAN PRESIDENT’S SPEECH BEFORE THE JAPANESE PARLIAMENT: A PRAGMATIC APPRAISAL - KOUTCHADE, INNOCENT SOUROU; Dadjo, Servais D. Y.; YOKOSSI, Tchorkpa Daniel (My University, 2022)
This study examines speech acts in the Ukrainian President’s speech held before the Japanese parliament on Wednesday, March 23, 2022 from a pragmatic perspective. The investigation seeks to decipher President Volodymyr Zelensky’s encoded messages in the above mentioned speech to make sense of his real political and diplomatic intentions behind it. To attain these objectives, the study has employed the mixed quantitative and qualitative methodology. Among other important findings made by the study, President Volodymyr Zelensky has used representative speech acts overridingly to account for the ongoing war drawbacks on Ukraine civilians, the environment, and mankind not only today, but also in the long run. His use of these speech acts has allowed to decode the message that the ongoing war has to be regarded not just as Ukraine’s business but as a misfortune befalling the globe owing to the boundless scope of its ravages. In that regard, President Volodymyr Zelensky recommends, from his disappointing biter experience of the ongoing war, through directive speech acts that nations world wide join hands and efforts to develop new security guarantees, and reform the existing international institutions in order to act preventively and strongly every time peace is threatened. He pledged via commissive speech acts to perform amazing feats together with Japan for the sake of peace and security worldwide beseeching them to continue rallying round Ukraine not only in this war time but even after.
Keywords: Pragmatics; speech act; study; Ukraine; war.